Predictive value of angiogenic factors, clinical risk factors and uterine artery Doppler for pre-eclampsia and fetal growth restriction in second and third trimester pregnancies in an Ecuadorian population. (16th February 2016) - Kienast, Carolin; Moya, Walter; Rodriguez, Oswaldo; Jijón, Alfredo; Geipel, Annegret
Abstract: Objective : To evaluate the performance of angiogenic factors, maternal risks and uterine artery Doppler (UAD) in the prediction of pre-eclampsia (PE) and fetal growth restriction (FGR) in a high-risk Ecuadorian population. Methods : Patients with singleton pregnancies ( n  = 346) were investigated at two clinical visits (18–25 weeks and 28–32 weeks). Mean uterine artery (UA), pulsatility index (PI) and maternal biomarkers (soluble fms-like tyrosine kinase-1, placental growth factor, sFlt-1/PLGF ratio) were obtained. The main endpoints were PE and FGR. UA PI and angiogenic factor levels were compared for the groups with PE ( n  = 34), FGR ( n  = 26), PE & FGR ( n  = 14) and controls ( n  = 272). Multivariable stepwise logistic regression was used to construct prediction models. Results : Pregnancies with either FGR or PE & FGR exhibited in the second trimester a significantly higher mean UA PI and sFlt-1/PLGF ratio and lower PLGF values compared to controls. In the third trimester, all groups with adverse outcome demonstrated significantly lower PLGF levels and a higher sFlt-1/PLGF ratio compared to normal pregnancies. Differences were most pronounced for pregnancies that developed PE and FGR for both time intervals. The combination of UAD and sFlt-1/PLGF ratio improved the predictive capacity for PE and FGR compared to each parameter alone. The best performance was obtained by integrating anamnestic risk factors, resulting in an area under the receiver operating curve for PE of 0.85 and 0.89 and for FGR of 0.79 and 0.77 in the second and third trimester, respectively. Conclusion : In a high-altitude Ecuadorian population, angiogenic factors and UA PI were useful tools in the prediction of PE and/or FGR. The highest performance was achieved by the combination of these factors, including obstetric and medical history.